2017
DOI: 10.1007/s13105-016-0545-x
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 modulates gene expression of proteins involved in inflammation, cytoskeleton, and liver architecture

Abstract: Even though the liver synthesizes most of circulating IGF-1, it lacks its receptor under physiological conditions. However, according to previous studies, a damaged liver expresses the receptor. For this reason, herein, we examine hepatic histology and expression of genes encoding proteins of the cytoskeleton, extracellular matrix, and cell-cell molecules and inflammation-related proteins. A partial IGF-1 deficiency murine model was used to investigate IGF-1’s effects on liver by comparing wild-type controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
(93 reference statements)
1
24
0
1
Order By: Relevance
“…53 Besides, Lara-Diza et al have uncovered that the IGF1 could regulate the expression of the IGF1 receptor and acute-phase inflammation mediators, which aggravate cell damage through oxidative stress pathway. 54 SELE has been demonstrated the function of assembling leukocytes at inflammatory sites through promoting the adhesion of cells. 55 Some studies have also reported that SELE-mediated adhesion of leukocytes or tumour cells to the vascular endothelium was an important progress in the initiation of inflammatory response and metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…53 Besides, Lara-Diza et al have uncovered that the IGF1 could regulate the expression of the IGF1 receptor and acute-phase inflammation mediators, which aggravate cell damage through oxidative stress pathway. 54 SELE has been demonstrated the function of assembling leukocytes at inflammatory sites through promoting the adhesion of cells. 55 Some studies have also reported that SELE-mediated adhesion of leukocytes or tumour cells to the vascular endothelium was an important progress in the initiation of inflammatory response and metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings are difficult to explain, some facts shed light over them. First of all, previous work using this same experimental model found that the single partial IGF-1 deficiency was associated with an altered structure of several organs, such as the brain [ 26 ], liver [ 25 ], and testicle [ 30 ]. Furthermore, the present study shows that hearts belonging to non-treated IGF-1-deficient mice overexpress Serpine1 and Serpinh1 , being sensitive to IGF-1 replacement therapy ( Fig 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported [ 1 , 25 , 26 ], heart mRNA was isolated from animals belonging to the three experimental groups in accordance with the protocol outlined in RNAqueousH-Micro Kit (Ambion, USA). Technical procedures for microarray analysis, including quality control of mRNA, labeling, hybridization and scanning of the arrays were performed according to standard operating procedures for Affymetrix protocols (GeneChipH Expression Analysis Manual, Affymetrix, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The role of IGF-1 in adult astrocytes seems to be limited to modulate tissue damage response, where reactive astrocytes express high levels of IGF1R [120,121] and IGF-1 [122]. Likewise, hepatocytes in damaged liver express IGF1R, a circumstance not observed under normal conditions [123][124][125]. In this context, proinflammatory signals activate astrocytes, turning them into activated pro-inflammatory cells that will secrete several factors (e.g.…”
Section: Igf-1 Actions In the Central Nervous Systemmentioning
confidence: 99%